Wintertime meso-scale horizontal distribution of large tintinnids in the southern Yellow Sea - 张翠霞 张武昌 肖天 吕瑞华 孙松 宋微波 (Chinese journal of oceanology and limnology, 2009)
Spatial distribution of some large tintinnid species （nominally 〉 76 μm） is investigated on samples vertically towed in the southern Yellow Sea in winters of 2001 to 2004. Nine tintinnid species are recorded： Codonellopsis morchella, Stenosemella pacifica, S. steini, Tintinnopsis schotti, T. radix, T. karajacensis, Eutintinnus tenuis, Parafavella sp., Leprotintinnus neriticus, of which C. morchella and T. radix dominated in the warm tongue-shaped zone of the Yellow Sea Warm Current （YSWC）, and S. pacifica is the next in abundance. Our study shows that these tintinnids occur repeatedly in certain special distribution patterns.